PERANCANGAN WEBSITE MULTIMEDIA INTERAKTIF SEBAGAI MEDIA PROMOSI DAN INFORMASI DI WARUNG KOP I JURNALIS MEDAN - Fauzul Zikri; Ricky Ramadhan harahap; Rahmadani (CV. Hawari, 2026)
The development of information and communication technology encourages business actors to utilize digital media as an effective means of promotion and information delivery. Warkop Jurnalis Medan, as a local culinary business, still relies on conventional promotional media, which limits the reach of information to consumers. This study aims to design an interactive multimedia website that functions as a promotional and information medium for Warkop Jurnalis Medan. The research method used is the System Development Life Cycle (SDLC) method, which includes the stages of requirements analysis, design, implementation, and testing. The website is designed by integrating multimedia elements such as text, images, video, and interactive animation to enhance user engagement. The results of this study indicate that the interactive multimedia website is capable of presenting information on menus, prices, locations, and the coffee shop's atmosphere in a more attractive and easily accessible manner for the public. With this website, it is expected to increase promotional effectiveness, expand marketing reach, and boost consumer interest in visiting Warkop Jurnalis Medan.